New Clinical Classification for Ventricular Free Wall Rupture following Acute Myocardial Infarction - Wei Gong; Shaoping Nie (Cardiovascular Therapeutics)
Ventricular free wall rupture (FWR) is a catastrophic complication after acute myocardial infarction (AMI). However, patients with FWR die of cardiac tamponade secondary to intrapericardial hemorrhage that can be treated if properly diagnosed. Unfortunately, FWR was still not diagnosed and classified quickly and accurately. The aim of this study was to present a new clinical classification for FWR. Seventy-eight patients with FWR after STEMI were enrolled in the study. We classified FWR, according to clinical situations after onset, into the cardiac arrest type, unstable type, and stable type. The cardiac arrest type was the most common type, accounting for about 83.3%. 90.8% of patients of this type were complicated with electromechanical dissociation at the time of FWR onset, and 100% of patients of this type died in the hospital. The unstable type was characterized by sudden clinical condition changes with moderate/massive pericardial effusion. In this study, 9.0% of patients were diagnosed as the unstable type. The average time from onset to death was 4.5 hours. This period was the “golden time” to rescue such patients. The stable types usually have stable hemodynamics, but may worsen, requiring rigorous detection of pericardial effusion and vital signs. In this study, 7.7% of patients were diagnosed as the stable type, and 83.5% of them survived in the hospital. The new clinical classification provides a basis for clinical diagnosis and treatment of FWR. The clinical application of the new classification is expected to improve the prognosis of FWR patients.